1994
DOI: 10.1029/94jd01024
|View full text |Cite
|
Sign up to set email alerts
|

Satellite analysis of the severe 1987 forest fires in northern China and southeastern Siberia

Abstract: Abstract. Meteorological conditions, extremely conducive to fire development and spread in the spring of 1987, resulted in forest fires burning over extremely large areas in the boreal forest zone in northeastern China and the southeastern region of Siberia. The great China fire, one of the largest and most destructive forest fires in recent history, occurred during this period in the Heilongjiang Province of China. Satellite imagery is used to examine the development and areal distribution of 1987 forest fire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
154
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(159 citation statements)
references
References 16 publications
(5 reference statements)
2
154
1
Order By: Relevance
“…Now it is established that pyroCb activity is sufficiently frequent that a measurable stratospheric increase in aerosols attributable to this process occurred in 1989-91, 1992 (Livesey et al 2004), 1998 (Fromm et al 2000(Fromm et al , 2005, and 2001-04 (Fromm et al 2006(Fromm et al , 2008aCammas et al 2009). Unpublished analyses of satellite data (e.g., SAGE II aerosol profiles and imager data) have also revealed pyroCbs and stratospheric aerosol layers that are attributable to the Great China Fire in May 1987 (Cahoon et al 1994) and the Yellowstone fires of 1988 (Alexander 2009). Hence, it can be concluded that for six consecutive years (1987-92) the pyroCb phenomenon was present and its stratospheric impact was identifiable.…”
Section: Pyroconvection In 2002mentioning
confidence: 99%
“…Now it is established that pyroCb activity is sufficiently frequent that a measurable stratospheric increase in aerosols attributable to this process occurred in 1989-91, 1992 (Livesey et al 2004), 1998 (Fromm et al 2000(Fromm et al , 2005, and 2001-04 (Fromm et al 2006(Fromm et al , 2008aCammas et al 2009). Unpublished analyses of satellite data (e.g., SAGE II aerosol profiles and imager data) have also revealed pyroCbs and stratospheric aerosol layers that are attributable to the Great China Fire in May 1987 (Cahoon et al 1994) and the Yellowstone fires of 1988 (Alexander 2009). Hence, it can be concluded that for six consecutive years (1987-92) the pyroCb phenomenon was present and its stratospheric impact was identifiable.…”
Section: Pyroconvection In 2002mentioning
confidence: 99%
“…In total, 1.53 million hectares were charred by fires in 1987, which was the most destructive fire year in China's history, with a specific larger fire in May that burned 1.33 million hectares alone. Extreme meteorological conditions, in combination with the lack of accessibility, resulted in large, high-intensity crown fires throughout China's boreal forests in 1987 [44]. Snowfall over the northern China was typically light during the winter of 1986-1987, and the snow cover had disappeared by early April southeast of Lake Baikal and along the Amur River.…”
Section: Determination Of Emission Factors (Ef)mentioning
confidence: 99%
“…Particularly during the spring fire season, there are always serious large forest fire events. For example, on 6th May 1987, a catastrophic fire occurred on the northern slopes of the GXM, which burned a total area of 1.3ˆ10 6 ha, with disastrous effects on the forest composition and structure, ecosystem processes and the landscape pattern [44]. The wildfire that broke out in Jinhe and Genhe counties on 5 May 2003 burned 7.9ˆ10 4 hectares, including 6.3ˆ10 4 hectares of forest areas, with an economic loss of more than 198 million RMB [44].…”
Section: Determination Of Emission Factors (Ef)mentioning
confidence: 99%
“…Large areas of the boreal forest zone, which natural fire have shaped over several millennia, are burned annually. Industrial and recreational use of boreal forests and forest fire suppression capabilities have dramatically increased over the past century [4]. Northeast China maintains abundant forest resources, with a forest area of ~47.0 × 10 4 km 2 , occupying 31% of China's total forest area [5].…”
Section: Introductionmentioning
confidence: 99%